Anthropogenic influence on the environmental health along Montenegro coast based on the bacterial and chemical characterization. (15th February 2021) - Jokanović, Sandra; Kajan, Katarina; Perović, Svetlana; Ivanić, Maja; Mačić, Vesna; Orlić, Sandi
Abstract: Coastal marine sediments are particularly exposed to human activities. The function of a coastal ecosystem is largely affected by eutrophication, wastewater discharges, chemical pollution, port activities, industry and tourism. Bacterial classification can be used as a measure in assessing the harmful effects on the ecosystem. This study provided insight into the environmental health of the coastal region of Montenegro analyzing the possible impact of PAHs and PCBs upon the bacterial community diversity and function as well as nutrients. Two stations at the shipyards were defined as very high PAH polluted together with PCB concentration exceeding threshold values. The bacterial community at the OTU level clustered together all stations except the most polluted site (SBL), the main tourist destination in Montenegro (BDV) and the estuary site (ADB) forming the independent clusters. Bacterial community based on the OTU level was driven by PAHs, TOC and silt content. The lowest richness and diversity were indicated at the site with the highest concentration of PAHs and PCBs with the highest abundance of Alphaproteobacteria followed by Gammaproteobacteria . OTUs affiliated to phyla BRC1, Dadabacteria and Spirochaetes were present with a total abundance higher than 1% only at the most polluted site indicating their persistence and possible potential for degradation of aromatic compounds. To compare functional capabilities potentially related to biodegradation of aromatic compounds and active transport systems, PICRUSt was used to predict metagenomes of the sediments. From our data, we identified specific bacterial community and predicted metabolic pathways that give us a picture of the environmental health along the coast of Montenegro, which provides us a new insight into human-induced pollution impacts on the coastal ecosystem. Graphical abstract: Image 1 Highlights: Total PAHs, TOC and silt are potential drivers of the bacterial community on the OTU level. The high concentration of PAHs and PCBs influenced the lowest richness and diversity. High differences in the functional capabilities of bacterial communities were recorded.